(untitled) (Journal of Management and Business Education, 2019)
In this research, it has been analyzed the use of current news from specialized press as an active didactic tool; Being focused on a competency-based framework, active and participatory methodology for university students. The rubrics are used as competency assessment tool, providing transparency to the process and making it suitable for being used in the classroom. Specifically, the transversal competence of analysis and synthesis allows us to identify the key elements of a specific situation. Current news is shown as a didactic tool that creates an environment conductive to learn, assuming a constructivist approach to competencies. Students of Business Economics were asked to analyze and synthesize some current news. Later, were assessed various aspects such as their compliance degree, motivation, interest and perceived utility. The results show a positive predisposition of the students using news, linking the socioeconomic reality with their academic knowledge.